2021
DOI: 10.3390/e23040462
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Martensitic Intercalations in Magnetic Shape Memory NiCoMnAl Multilayered Films

Abstract: Hysteresis and transformation behavior were studied in epitaxial NiCoMnAl magnetic shape memory alloy thin films with varying number martensitic intercalations (MIs) placed in between. MIs consists of a different NiCoMnAl composition with a martensitic transformation occurring at much higher temperature than the host composition. With increasing number of intercalations, we find a decrease in hysteresis width from 17 K to 10 K. For a large difference in the layers thicknesses this is accompanied by a larger am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The stoichiometry of the compound in these two layers is chosen in such a way that their individual thermal hysteresis does not overlap, as depicted in Figure 1a. More details about the transition temperatures and the measured thermal hysteresis can be found in our previous study [19]. An illustration of the initially sputtered multilayer system is given in Figure 1b.…”
Section: Methodsmentioning
confidence: 91%
See 2 more Smart Citations
“…The stoichiometry of the compound in these two layers is chosen in such a way that their individual thermal hysteresis does not overlap, as depicted in Figure 1a. More details about the transition temperatures and the measured thermal hysteresis can be found in our previous study [19]. An illustration of the initially sputtered multilayer system is given in Figure 1b.…”
Section: Methodsmentioning
confidence: 91%
“…In a previous study, we have demonstrated that the thermal hysteresis could be decreased by preparing off-stoichiometric NiCoMnAl multilayer systems, which consist of alternating grown martensite intercalations (MIs) and active transforming austenitic layers (ALs) [19]. This MIs have shown to be beneficial for transforming films, because the formation energy during martensite nucleation is reduced.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation